Sustainable mobility in Munich. Exploring the role of discourse in policy change. - Tschoerner-Budde, Chelsea (Springer VS, 2019)
The author analyzes discourse in two cases of sustainable mobility policymaking in Munich: cycling promotion and electric mobility promotion. Both cases revealed that the formation and integration of a new, socially driven discourse on everyday mobility was necessary for policy change. Historically, transport policy has been structured to improve flow and manage transport systems. The new "everyday mobility cultures" approach presents a potential framework for improving policymaking and fostering a transition in the transport sector.
Keywords: Verkehr; Verkehrspolitik; Verkehrsplanung; Stadtplanung; Stadtverkehr; Individualverkehr; Mobilität; Verkehrswende; Fallstudie; Fahrradverkehr; Elektromobilität; Nachhaltige Mobilität; Alltagsmobilität; Radverkehrsförderung